Determinants of implementing patient-centred care in developing countries: a case study of Kahama Municipal Hospital in Tanzania - Doreen Mloka; Lazaro Amon Solomon Haule; Renatha Silo Joseph (BMJ Open)
Background Patient-centred care (PCC) is one of the six key attributes of healthcare quality. However, despite its significant contribution to improving healthcare quality, PCC is often poorly implemented. This study aimed to explore the determinants of effective PCC implementation among healthcare providers at Kahama Municipal Hospital in Tanzania.Objective To explore the determinants influencing the effective implementation of PCC among healthcare providers at Kahama Municipal Hospital in Tanzania.Design A qualitative approach was used, with 21 healthcare providers recruited through purposive and convenience sampling methods. Data were collected through focus group discussions and key informant interviews, and content analysis was employed to analyse the data.Setting The study was conducted at Kahama Municipal Hospital, in the Kahama Municipal Council of the Shinyanga region, Tanzania, from February to June 2019. As a referral hospital, Kahama Municipal Hospital serves a vast catchment area, including rural and semiurban communities across more than eight regions in Tanzania’s Lake and Western zones.Results The study identified several factors related to healthcare professionals, including awareness of PCC, staff motivation, heavy workload, professional competencies and effective communication. Organisational-related determinants, such as the absence of ethical guidelines, a lack of a clear organisational culture and the absence of specific policies and guidelines on PCC, were also found to affect its effective implementation.Conclusion PCC is recognised at Kahama Municipal Hospital, but key barriers hinder its implementation, including unclear policies, lack of a PCC-focused vision, staff shortages, excessive workloads, low motivation, limited practical exposure and communication issues. To improve PCC implementation, healthcare policymakers and hospital administrators should: (1) establish clear PCC policies, (2) integrate a patient-centred vision into leadership, (3) address workforce shortages, (4) provide targeted training on PCC and (5) boost staff motivation through recognition and career development. Implementing these measures will improve care quality and health outcomes. Further large-scale research is needed to assess PCC implementation across Tanzania and guide national policy.